Hubungan Kadar Natrium, Kalium dan Klorida Pada Pasien Hipertensi Di Rumah Sakit Umum Daerah Koja Jakarta Utara - Ellis Susanti; Atna Permana; Sumiati Bedah (Anakes : Jurnal Ilmiah Analis Kesehatan, 2025)
Hypertension is a very common and quite high disease problem in the world. -The prevalence of hypertension in the population aged over 18years is still quite high at 30.8% in 2023 (Riskesdas 2023). One of the causes of hypertension is due to an increase in Sodium and Chloridelevels and a decrease in Potassium levels. This study aims to determine the description of Sodium, Potassium and Chloride levels in emergencyhypertension patients at Koja Regional General Hospital, North Jakarta. The research method used a cross-sectional with a sample of 100hypertension patients who underwent  sodium, Potassium  and  Chloride  examinations  at Koja  Regional General Hospital, East Jakarta. .The most abnormal Sodium results were in the early elderly age group 60-65 years (21%), Potassium (42%) and Chloride (30%) in the Pre- elderlyage group (46-59 years). The most abnormal Sodium results were in women (24%), Potassium in men (46%), while Chloride was obtainedequally between men and women (24%). Abnormal sodium (27%) and potassium (37%) results were most common in patients with stage I hypertension, while abnormal chloride results were most common in pre-hypertension patients (50%). It is recommended that patients with hypertension have their sodium, potassium, and chloride levels checked for monitoring and evaluation, as well as for monitoring the effectivenessof treatment.   Keywords: Chloride, Hypertension, Potassium, Sodium